The straw bale house - 20160731 frey50; Steen, Athena Swentzell, 1961- (White River Junction, Vt. : Chelsea Green Pub. Co., 1994)
Whether you build an entire house or something more modest - a home, office or studio, a retreat cabin or guest cottage - plastered straw bale construction is an exceptionally durable and inexpensive option. What's more, it's fun, because the technique is easy to learn and easy to do yourself. And the resulting living spaces are unusually quiet and comfortable.
Keywords: Straw bale houses -- Design and construction; Woningen; Stro; Bouwmaterialen